The feasibility of occupational therapy using Zones of Regulation™ Concepts in an equine environment - Peters, B. Caitlin; Gabriels, Robin L.; Schmid, Arlene A.; Pan, Zhaoxing; Merritt, Tamara; Hoffman, Arielle; Hepburn, Susan (Frontiers in Psychiatry, 2024)
Introduction The current paper aimed to assess the feasibility of a modified intervention protocol named “Occupational Therapy using Zones of Regulation Concepts in an Equine Environment” (OT-ZOR Equine). Methods A single arm A-B feasibility study was conducted, involving 14 autistic youth ages 6-13 years who first received 10-weeks of occupational therapy without horses (OT-ZOR Clinic) followed by 10-weeks of OT-ZOR Equine. Results All participants completed the study and attended 95% of OT-ZOR Equine sessions. Occupational therapists maintained 91% fidelity to the OT-ZOR Equine intervention protocol and there were no serious adverse events. All participants’ caregivers and study occupational therapists rated being satisfied or very satisfied with the OT-ZOR Equine intervention. Youth demonstrated improved self-regulation following participation in the OT-ZOR Clinic and OT-ZOR Equine interventions. However, participants’ social functioning only improved after OT-ZOR Equine. Discussion This study demonstrated that OT-ZOR Equine is feasible to implement, acceptable to recipients and providers, and may offer additive benefits in social functioning compared to occupational therapy intervention without horses. The current study provides a foundation for future efficacy research aimed at quantifying additive benefits of integrating horses into occupational therapy for autistic youth.